Depression and Anxiety Prevention Based on Cognitive Behavioral Therapy for At-Risk Adolescents: A Meta-Analytic Review - Rasing, Sanne P. A.; Creemers, Daan H. M.; Janssens, Jan M. A. M.; Scholte, Ron H. J. (Frontiers in Psychology, 2017)
Depression and anxiety disorders are among the most common mental disorders during adolescence. During this life phase, the incidence of these clinical disorders rises dramatically, and even more adolescents suffer from symptoms of depression or anxiety that are just below the clinical threshold. Both clinical and subclinical levels of depression or anxiety symptoms are related to decreased functioning in various areas, such as social and academic functioning. Prevention of depression and anxiety in adolescents is therefore imperative. We conducted a meta-analytic review of the effects of school-based and community-based prevention programs that are based on cognitive behavioral therapy with the primary goal preventing depression, anxiety, or both in high risk adolescents. Articles were obtained by searching databases and hand searching reference lists of relevant articles and reviews. The selection process yielded 23 articles in the meta-analyses. One article reported on two studies and three articles reported on both depression and anxiety. This resulted in a total of 27 studies, 16 on depression and eleven on anxiety. For depression prevention aimed at high risk adolescents, meta-analysis showed a small effect of prevention programs directly after the intervention and at six months follow-up, but no effect at twelve months follow-up. For anxiety prevention aimed at high risk adolescents, no short-term effect was found, nor effects at six or twelve months follow-up. Although effect sizes on depression symptoms were small, current findings support the use of depression prevention programs because mental health of adolescents seems to improve. However, it also indicates that there is still much to be gained for prevention programs aimed at anxiety prevention. Current findings and possibilities for future research are discussed in order to further improve the effectiveness of targeted prevention on internalizing disorders.